Resistin gene polymorphisms and serum lipid levels in acne vulgaris: a case-control study in Egyptian patients - Hossam M Abdel Wahab; Maha H Ragaie; Shereen S Gaber; Rehab H.A Younis (Wolters Kluwer Medknow Publications, 2019)
Background Acne vulgaris is a multifactorial inflammatory disease. Resistin gene is believed to play a role in inflammatory diseases by triggering the release of some cytokines. Objective The aim was to investigate resistin gene polymorphisms in patients with acne and the relation between the gene polymorphisms and serum lipid levels in Egyptian patients with acne. Patients and methods A total of 50 Egyptian patients with acne vulgaris and 50 healthy controls were enrolled in this case-control study. Global acne grading system was used to assess the severity of acne. PCR-RFLP technique was used to detect polymorphisms of RETN +299G>A and RETN −420C>G, and the serum lipids are measured in all patients and controls. Results RETN gene polymorphisms at −420C>G genotype distribution showed a significant difference between patients and control groups in CG and GG genotypes. Participants carrying G allele were significantly more likely to develop acne vulgaris. There was a significant difference between patients and control groups in the frequency of distribution of GA and AA genotypes in RETN gene polymorphisms at +299G>A. There were significant positive correlations between both RETN gene polymorphisms and acne severity, total cholesterol, and low-density lipoprotein. Conclusion RETN gene polymorphisms at −420C>G and +299G>A are significantly associated with serum lipids and severity of acne vulgaris in Egyptian populations. Thus, RETN may play a central role in acne pathogenesis through its dual effects on both lipid metabolism and inflammation.